Regional Development in Hungary and Its Preparation for the Structural Funds - Rave, Simone (Discussion Papers, 1999)
In this discussion paper attention will be paid to the problems for Hungary in adopting these requirements with regard to regional policy. The paper will concentrate mainly on the adoption problems at the regional level and not on the macro level. The first chapter will give a short summary of the history behind the Structural Funds. In the second chapter shortly attention will be paid to the current situation in Hungary. In 1996 Hungary made the first step by introducing the Act on Regional Policy and Physical Planning. Although the institutional structure has been laid down it appears very difficult to implement the Act in a proper way. Therefore the third chapter will deal with two case studies; Baranya and Szabolcs-Szatmár-Bereg. During a research in Hungary about the implementation of the Act of 1996 there have been several interviews in these two counties, to analyse the present situation in regional policy. Since Hungary will be entirely Objective 1, chapter 4 will deal with a case study of the former Objective 1 region Ireland. This case study won’t function as a model for Hungary how to implement the Structural Funds, but it will function as an example. Learning the strengths and weaknesses of another system can be useful when developing and adopting an own system. Finally, chapter 6 will highlight the main conclusions with regard to the present situation in regional policy in Hungary and will put forward some solutions for the current problems.